The Discourse Functions of and in the Australian Students’ Presentations - Rusdi, Rusdi (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2008)
And is generally known as a connector which relates parallel information or ideas. In the discourse contexts, and is used differently. This article presents the discourse functions of and as a discourse marker in the presentations made by Australian students in academic settings. It was identified that and has four different discourse functions: i) linking events within a discourse topic; ii) introducing a new topic; iii) signalling a summary; and iv) signalling a speaker’s retaking a turn.